Plan de Manejo Agroecológico y Administrativo de la Unidad Educativa de Producción del Colegio Técnico Agropecuario Macará perteneciente a la Parroquia y cantón Macará, Provincia de Loja, 2011 - Alvarez Orozco, Amable Hernan (2014)
The as well practices in agricological terms that permit us to obtain a better production per unit of superficial, the cost of production are going down avoiding the use of insums and qualified hand workers, then we can obtain organic products; The integral Farm involve cultural labors pequary of each property, taking in mind the activities like the stages of seeding, parcel disposition, ancient knowledge, moon calendar, selection of seeds, seedtime, seed intensity, intensive fat grow, prophylaxis, and cleaning of barn yards, agro ecological management, of soil, get an optimum use of water, plants, animals, integrate control of banes and sickness, post harvest time, and commercialization. The agro ecological and administrative plan of management of the Technical Agropecuarial Macará School, belong to canton and parish of Macará as scenario of acquiring knowledge; must offer to curriculum of competencies established in the Ministerial Accordance No. 539. And ambitiously pretend that the achieved competencies by the graduated students, could get go inside to the labors activities as producers and to establish a proposal in the agropecuary ambit and microempresarial, so the student can realize their self experiences, then Hoe to sociabilize inside of the society and through the proposals permit diffuse the knowledge in the best way.